2011
DOI: 10.1016/j.peva.2011.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Stability analysis of multiserver discrete-time queueing systems with renewal-type server interruptions

Abstract: For many queueing systems the server is not continuously available. Service interruptions may result from repair times after server failures, from planned maintenance periods or from periods during which customers from other queues are being served. These service interruptions cause an overall performance degradation which is most striking when interruptions can start while a customer is being served and his service has to start all over after the interruption. This is the so-called preemptive repeat service d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…The model in [62] is a variant of this, where the service-time distribution is general and both the arrival process and the serverinterruption process are dependent on a common underlying finite-state Markov chain. Also relevant in this context is [63], where sufficient conditions for system stability, both in the single-server and the multi-server case, are established under renewal assumptions for arrival, service and interruption processes.…”
Section: Discrete-time Modelsmentioning
confidence: 99%
“…The model in [62] is a variant of this, where the service-time distribution is general and both the arrival process and the serverinterruption process are dependent on a common underlying finite-state Markov chain. Also relevant in this context is [63], where sufficient conditions for system stability, both in the single-server and the multi-server case, are established under renewal assumptions for arrival, service and interruption processes.…”
Section: Discrete-time Modelsmentioning
confidence: 99%
“…1 such that .k/ i that are distributed as B .k/ . We then obtain, for an appropriate x 0 , the following lower bound for the probability (28) [where we also use Equation (29)]:…”
Section: Proof Let At the Instant T Bmentioning
confidence: 99%
“…Later on, Zhang et al [18] studied the noncooperative and cooperative strategies of customers in the context of a retrial queueing model where the server is subject to vacations, breakdowns and repairs. However, although more attention has been paid on the analysis of discrete time queueing models with unreliable server, such as Atencia and Moreno [1], Bruneel [2], Fiems et al [5][6], Moreno [9], Morozov et al [10], Vinck and Bruneel [14], Wang and Zhang [16][17], among others, it is found that there is no work concerning the equilibrium balking behavior in the discrete-time queues with server breakdowns and repairs.…”
Section: Introductionmentioning
confidence: 99%